Synthesis and Evaluation of Platinum Nanoparticles Using F. Carica Fruit Extract and Their Antimicrobial Activities - Jenan Hussien Taha; Nada Khudair Abbas; Azhar A. F. Al- Attraqchi (مجلة بغداد للعلوم, 2023)
Abstract